A Theory of Bioethics - DeGrazia, David (Humanities, 2021)
Intended for students, scholars, and others interested in bioethics, this volume offers a compelling theory of bioethics while eliciting practical implications for issues including medical assistance-in-dying, the right to health care, abortion, animal research, and the definition of death. This title is available as Open Access on Cambridge Core.